Ultrahigh-temperature-resistant polyimide film and preparation method thereof
By introducing metal ions into the polyamic acid solution to form metal-organic coordination bonds, the problem of insufficient thermal stability and mechanical properties of the polyimide film under high temperature conditions is solved, and the ultra-high temperature resistance of the polyimide film is improved.
Patent Information
- Application Number
- CN202510136665.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-18
AI Technical Summary
The lack of thermal stability and mechanical properties of polyimide films under high temperature conditions limits its application in high-tech fields.
By introducing metal ions into the polyamic acid solution, metal-organic coordination bonds are formed, and the thermal stability and mechanical properties of the polyimide film are improved. The specific steps include preparing the blending and coordination of the metal ion dispersion and the polyamic acid solution and dehydration treatment, followed by vacuum defoaming and high-temperature imidation treatment to prepare an ultra-high temperature resistant polyimide film.
The 5% thermal weight loss temperature of the polyimide film is significantly improved to reach ≥570℃, and its glass transition temperature and mechanical properties are enhanced, with excellent high temperature resistance.
Smart Images

Figure BDA0005263472210000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyimide film preparation, and in particular relates to an ultra-high temperature resistant polyimide film and a preparation method thereof. Background Art
[0002] Polyimide film (PI film) is currently the best performing film insulation material and one of the most expensive film materials in the world. Together with carbon fiber and aramid fiber, it is considered to be the three major bottleneck key polymer materials that currently restrict the development of high-tech industries in my country.
[0003] There are many synthetic routes for the synthesis of polyimide (PI). At present, PI is often obtained by further imidization by the reaction of dianhydride and diamine to form polyamic acid. It has excellent comprehensive performance. However, polyimide still needs to be further improved to improve its performance in many high-tech fields. For example, when it comes to large-scale integrated circuits, the polyimide substrate film must have low dielectric constant and high temperature resistance. Current research has shown that the introduction of metal ions into polymers to form coordination bonds has a significant improvement effect on the mechanical and physical properties of polymers such as heat resistance, impact resistance, and tear resistance.
[0004] According to the organic-metal coordination theory, when metal exists in the polymer resin phase in the form of ions, due to the strong reducing ability of metal ions (especially transition metals) themselves, they will form coordinated covalent bonds with atoms such as N and O in organic polymers. This behavior is generally called metal-organic complex bonding, thus forming a special metal-organic complex (Metal-Organic Complex, MOC). Metal-organic complex bonding is a strong chemical bond, and the use of metal complex organic polymers is a very effective way to improve organic materials. By introducing metal ions to form coordination bonds, polyimides with enhanced performance can also be obtained. However, the difficulty lies in the fact that metal compounds (usually salts) are difficult to completely dissociate in the oil phase (i.e., organic solvents) to precipitate metal ions, so it is difficult to co-dissolve (or eutectic) with organic polymers and mix evenly to form metal-organic complexes, so it is greatly limited in practical industrial applications. Summary of the invention
[0005] The purpose of the present invention is to provide an ultra-high temperature resistant polyimide film and a preparation method thereof, so as to improve the high temperature resistance of the polyimide film.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] The present invention provides a method for preparing an ultrahigh temperature resistant polyimide film, comprising the following steps:
[0008] Step 1, preparing a metal ion dispersion: dissolving a soluble metal salt in water, adding a polar organic solvent, and mixing to prepare a metal ion dispersion for later use;
[0009] Step 2, preparing a polyamic acid solution: polycondensing a dianhydride monomer and a diamine monomer in a polar organic solvent to form a polyamic acid solution for later use;
[0010] Step 3, blending, coordination and dehydration treatment: heating the polyamic acid solution to 80-90° C., adding the metal ion dispersion prepared in step 1 thereto to obtain a mixed solution, stirring at a constant temperature and then cooling to room temperature to obtain a composite polyamic acid solution;
[0011] Step 4: vacuum degassing and film making: the composite polyamic acid solution is subjected to vacuum degassing treatment, followed by film coating, and subjected to high-temperature imidization treatment to obtain a polyimide film.
[0012] Furthermore, the soluble metal salt is 0.1%-0.5% of the total mass of the metal ion dispersion. When the concentration of the metal salt is too low, it is difficult for the metal salt to fully contact with the polyamic acid, and the content of the organic-metal complex formed is limited. When the concentration is too high, there are excess metal ions that do not form coordination bonds with the polyamic acid, and the free metal ions will interfere with the arrangement of the polymer chain, thereby increasing the brittleness of the material or reducing the ductility.
[0013] Furthermore, the mass ratio of water to polar organic solvent in the metal ion dispersion is 0.9-1:9.
[0014] Water can be used as a solvent for dissociating soluble metal salts. The water content in the metal ion dispersion should not be too much. Too much water will make it difficult to completely dehydrate, resulting in a decrease in the performance of the polyimide and a decrease in the film-making efficiency.
[0015] Furthermore, the soluble metal salt is one of copper sulfate, aluminum sulfate, iron sulfate and titanium sulfate.
[0016] Introducing metal ions into polyimide to form coordination bonds can effectively improve its thermal stability. After the introduction of metal ions, a coordination cross-linking network is formed between its molecular chains. The uncross-linked polyimide will show obvious thermal weight loss at around 400°C, mainly due to the decarboxylation cross-linking reaction of the side carboxyl group. After the carboxyl group and the metal ion are coordinated, the stability of the carboxyl group is enhanced, which can significantly increase its 5% thermal weight loss temperature. With the addition of metal ions, a three-dimensional cross-linked network structure based on the coordination effect of metal ions is formed in the system, which strengthens the interaction between the molecular chains, and improves its glass transition temperature and mechanical properties.
[0017] Furthermore, in step 1 and step 2, the polar organic solvent is one of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone. An organic solvent miscible with water is selected to uniformly disperse the components in the metal ion dispersion to avoid stratification.
[0018] Furthermore, in step three, the metal ion dispersion is 0.005%-0.02% of the total mass of the mixed solution.
[0019] Furthermore, in step three, the constant temperature stirring time is 30-150 minutes. In general, water vapor intrusion should be avoided during the synthesis of polyamic acid (PAA) to avoid viscosity reduction and mechanical and insulation properties after film formation. Therefore, deionized water in the metal ion dispersion must be removed before film coating to avoid the above-mentioned adverse effects or bubble rupture and other phenomena. By using high temperature (80-90°C) dehydration, the metal ions are retained in PAA to achieve coordination with the polymer molecular chain. The negative impact of moisture can be avoided.
[0020] Furthermore, the polyamic acid solution is obtained by a condensation synthesis reaction of 4,4'-diaminodiphenyl ether and pyromellitic dianhydride.
[0021] Furthermore, the temperature of the high temperature imidization treatment is set as follows:
[0022] Raise the temperature to 80℃ and keep it for 20 minutes, then raise the temperature to 130℃ and keep it for 20 minutes, and finally raise the temperature to 300℃ and keep it for 20 minutes.
[0023] The present invention also provides an ultra-high temperature resistant polyimide film, which is prepared by the preparation method as described above.
[0024] Furthermore, the thermal weight loss temperature of the ultra-high temperature resistant polyimide film when it loses 5% of its weight is ≥570°C.
[0025] Beneficial effects of the present invention:
[0026] (1) The present invention uses deionized water to completely dissociate the soluble metal salt, which is then mixed with an organic solvent to form an oil-water co-solvent, which is then blended into the polyimide resin system. This can achieve complete dissociation of the soluble metal salt, thereby forming a metal-organic complex and improving the thermal stability and mechanical properties of the polyimide film.
[0027] (2) The present invention removes moisture from the composite polyamic acid by high temperature (80-90°C), and utilizes the accelerated evaporation behavior of water at 80°C-90°C to perform dehydration treatment. The operation is simple, and the duration of the dehydration process needs to be strictly controlled. When the polyamic acid is exposed to high temperature for a long time, the molecular chain of the polyamic acid will continue to expand due to its own excessive energy storage, thereby causing agglomeration similar to gel. When the composite polyamic acid gradually forms a discontinuous phase such as a non-Newtonian fluid from the original continuous Newtonian fluid, the subsequent coating and film-forming process becomes more difficult. Reasonable control of the dehydration treatment time can ensure that the moisture is removed before coating while avoiding agglomeration. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] Preparation of polyamic acid solution:
[0031] 4,4'-diaminodiphenyl ether (ODA) was completely dissolved in N,N-dimethylacetamide (DMAC), and pyromellitic dianhydride (PMDA) in an amount equal to that of ODA was added. DMAC was added to adjust the solid content of the solution to 30%, and a polycondensation reaction was carried out at 10°C for 8 hours to obtain a polyamic acid solution.
[0032] Preparation of polyamide membrane:
[0033] Step 1, prepare a metal ion dispersion: completely dissolve 1g of titanium sulfate in 99g of deionized water, then add 900g of N,N-dimethylacetamide, mix and prepare a metal ion dispersion, wherein the titanium sulfate accounts for 0.1% of the total mass of the metal ion dispersion, and set aside;
[0034] Step 2, blending, coordination and dehydration treatment: the polyamic acid solution is heated to 80°C, and the metal ion dispersion prepared in step 1 is added thereto to obtain a mixed solution, wherein the metal ion dispersion accounts for 0.005% of the mass of the mixed solution, and the mixture is stirred at 80°C for 120 minutes and then cooled to room temperature to obtain a composite polyamic acid solution;
[0035] Step 3, vacuum degassing and film making: the composite polyamic acid solution is subjected to vacuum degassing treatment, and the degassing composite polyamic acid solution is scraped onto a high-temperature resistant boronized glass plate with a scraper, placed in an oven and heated to 80°C for 20 minutes, then heated to 130°C for 20 minutes, and finally heated to 300°C for 20 minutes to complete the high-temperature imidization treatment, the glass plate is taken out and the polyimide film is peeled off from the glass plate to obtain a polyimide film.
[0036] Example 2
[0037] The only difference from Example 1 is that in step 2, the metal ion dispersion is adjusted from 0.005% to 0.01% of the mass of the mixed solution, and the steps for preparing the polyamic acid solution are the same as in Example 1.
[0038] Preparation of polyamide membrane:
[0039] Step 1, prepare a metal ion dispersion: completely dissolve 1g of titanium sulfate in 99g of deionized water, then add 900g of N,N-dimethylacetamide, mix and prepare a metal ion dispersion, wherein the titanium sulfate accounts for 0.1% of the total mass of the metal ion dispersion, and set aside;
[0040] Step 2, blending, coordination and dehydration treatment: the polyamic acid solution is heated to 80°C, and the metal ion dispersion prepared in step 1 is added thereto to obtain a mixed solution, wherein the metal ion dispersion accounts for 0.01% of the mass of the mixed solution, and the mixture is stirred at 80°C for 120 minutes and then cooled to room temperature to obtain a composite polyamic acid solution;
[0041] Step 3, vacuum degassing and film making: the composite polyamic acid solution is subjected to vacuum degassing treatment, and the degassing composite polyamic acid solution is scraped onto a high-temperature resistant boronized glass plate with a scraper, placed in an oven and heated to 80°C for 20 minutes, then heated to 130°C for 20 minutes, and finally heated to 300°C for 20 minutes to complete the high-temperature imidization treatment, the glass plate is taken out and the polyimide film is peeled off from the glass plate to obtain a polyimide film.
[0042] Example 3
[0043] The only difference from Example 1 is that in step 2, the metal ion dispersion is adjusted from 0.005% to 0.02% of the mass of the mixed solution, and the steps for preparing the polyamic acid solution are the same as in Example 1.
[0044] Preparation of polyamide membrane:
[0045] Step 1, prepare a metal ion dispersion: completely dissolve 1g of titanium sulfate in 99g of deionized water, then add 900g of N,N-dimethylacetamide, mix and prepare a metal ion dispersion, wherein the titanium sulfate accounts for 0.1% of the total mass of the metal ion dispersion, and set aside;
[0046] Step 2, blending, coordination and dehydration treatment: the polyamic acid solution is heated to 80°C, and the metal ion dispersion prepared in step 1 is added thereto to obtain a mixed solution, wherein the metal ion dispersion accounts for 0.02% of the mass of the mixed solution, and the mixture is stirred at 80°C for 120 minutes and then cooled to room temperature to obtain a composite polyamic acid solution;
[0047] Step 3, vacuum degassing and film making: the composite polyamic acid solution is subjected to vacuum degassing treatment, and the degassing composite polyamic acid solution is scraped onto a high-temperature resistant boronized glass plate with a scraper, placed in an oven and heated to 80°C for 20 minutes, then heated to 130°C for 20 minutes, and finally heated to 300°C for 20 minutes to complete the high-temperature imidization treatment, the glass plate is taken out and the polyimide film is peeled off from the glass plate to obtain a polyimide film.
[0048] Example 4
[0049] The only difference from Example 2 is that in step 2, the constant temperature stirring at 80° C. for 120 min is adjusted to 30 min, and the steps for preparing the polyamic acid solution are the same as in Example 1.
[0050] Preparation of polyamide membrane:
[0051] Step 1, prepare a metal ion dispersion: completely dissolve 1g of titanium sulfate in 99g of deionized water, then add 900g of N,N-dimethylacetamide, mix and prepare a metal ion dispersion, wherein the titanium sulfate accounts for 0.1% of the total mass of the metal ion dispersion, and set aside;
[0052] Step 2, blending, coordination and dehydration treatment: the polyamic acid solution is heated to 80°C, and the metal ion dispersion prepared in step 1 is added thereto to obtain a mixed solution, wherein the metal ion dispersion accounts for 0.01% of the mass of the mixed solution, and the mixture is stirred at 80°C for 30 minutes and then cooled to room temperature to obtain a composite polyamic acid solution;
[0053] Step 3, vacuum degassing and film making: the composite polyamic acid solution is subjected to vacuum degassing treatment, and the degassing composite polyamic acid solution is scraped onto a high-temperature resistant boronized glass plate with a scraper, placed in an oven and heated to 80°C for 20 minutes, then heated to 130°C for 20 minutes, and finally heated to 300°C for 20 minutes to complete the high-temperature imidization treatment, the glass plate is taken out and the polyimide film is peeled off from the glass plate to obtain a polyimide film.
[0054] Example 5
[0055] The only difference from Example 2 is that in step 2, the constant temperature stirring at 80° C. for 120 min is adjusted to 60 min, and the steps for preparing the polyamic acid solution are the same as in Example 1.
[0056] Preparation of polyamide membrane:
[0057] Step 1, prepare a metal ion dispersion: completely dissolve 1g of titanium sulfate in 99g of deionized water, then add 900g of N,N-dimethylacetamide, mix and prepare a metal ion dispersion, wherein the titanium sulfate accounts for 0.1% of the total mass of the metal ion dispersion, and set aside;
[0058] Step 2, blending, coordination and dehydration treatment: the polyamic acid solution is heated to 80°C, and the metal ion dispersion prepared in step 1 is added thereto to obtain a mixed solution, wherein the metal ion dispersion accounts for 0.01% of the mass of the mixed solution, and the mixture is stirred at 80°C for 60 minutes and then cooled to room temperature to obtain a composite polyamic acid solution;
[0059] Step 3, vacuum degassing and film making: the composite polyamic acid solution is subjected to vacuum degassing treatment, and the degassing composite polyamic acid solution is scraped onto a high-temperature resistant boronized glass plate with a scraper, placed in an oven and heated to 80°C for 20 minutes, then heated to 130°C for 20 minutes, and finally heated to 300°C for 20 minutes to complete the high-temperature imidization treatment, the glass plate is taken out and the polyimide film is peeled off from the glass plate to obtain a polyimide film.
[0060] Example 6
[0061] The only difference from Example 2 is that in step 2, the constant temperature stirring at 80° C. for 120 min is adjusted to 90 min, and the steps for preparing the polyamic acid solution are the same as in Example 1.
[0062] Preparation of polyamide membrane:
[0063] Step 1, prepare a metal ion dispersion: completely dissolve 1g of titanium sulfate in 99g of deionized water, then add 900g of N,N-dimethylacetamide, mix and prepare a metal ion dispersion, wherein the titanium sulfate accounts for 0.1% of the total mass of the metal ion dispersion, and set aside;
[0064] Step 2, blending, coordination and dehydration treatment: the polyamic acid solution is heated to 80°C, and the metal ion dispersion prepared in step 1 is added thereto to obtain a mixed solution, wherein the metal ion dispersion accounts for 0.01% of the mass of the mixed solution, and the mixture is stirred at 80°C for 90 minutes and then cooled to room temperature to obtain a composite polyamic acid solution;
[0065] Step 3, vacuum degassing and film making: the composite polyamic acid solution is subjected to vacuum degassing treatment, and the degassing composite polyamic acid solution is scraped onto a high-temperature resistant boronized glass plate with a scraper, placed in an oven and heated to 80°C for 20 minutes, then heated to 130°C for 20 minutes, and finally heated to 300°C for 20 minutes to complete the high-temperature imidization treatment, the glass plate is taken out and the polyimide film is peeled off from the glass plate to obtain a polyimide film.
[0066] Example 7
[0067] The only difference from Example 2 is that in step 2, the constant temperature stirring at 80° C. for 120 min is adjusted to 150 min, and the steps for preparing the polyamic acid solution are the same as in Example 1.
[0068] Preparation of polyamide membrane:
[0069] Step 1, prepare a metal ion dispersion: completely dissolve 1g of titanium sulfate in 99g of deionized water, then add 900g of N,N-dimethylacetamide, mix and prepare a metal ion dispersion, wherein the titanium sulfate accounts for 0.1% of the total mass of the metal ion dispersion, and set aside;
[0070] Step 2, blending, coordination and dehydration treatment: the polyamic acid solution is heated to 80°C, and the metal ion dispersion prepared in step 1 is added thereto to obtain a mixed solution, wherein the metal ion dispersion accounts for 0.01% of the mass of the mixed solution, and the mixture is stirred at 80°C for 150 minutes and then cooled to room temperature to obtain a composite polyamic acid solution;
[0071] Step 3, vacuum degassing and film making: the composite polyamic acid solution is subjected to vacuum degassing treatment, and the degassing composite polyamic acid solution is scraped onto a high-temperature resistant boronized glass plate with a scraper, placed in an oven and heated to 80°C for 20 minutes, then heated to 130°C for 20 minutes, and finally heated to 300°C for 20 minutes to complete the high-temperature imidization treatment, the glass plate is taken out and the polyimide film is peeled off from the glass plate to obtain a polyimide film.
[0072] Example 8
[0073] The only difference from Example 2 is that in step 1, titanium sulfate is adjusted to copper sulfate, and the steps for preparing the polyamic acid solution are the same as in Example 1.
[0074] Preparation of polyamide membrane:
[0075] Step 1, prepare a metal ion dispersion: completely dissolve 1g of copper sulfate in 99g of deionized water, then add 900g of N,N-dimethylacetamide, mix and prepare a metal ion dispersion, wherein copper sulfate accounts for 0.1% of the total mass of the metal ion dispersion, and set aside;
[0076] Step 2, blending, coordination and dehydration treatment: the polyamic acid solution is heated to 80°C, and the metal ion dispersion prepared in step 1 is added thereto to obtain a mixed solution, wherein the metal ion dispersion accounts for 0.01% of the mass of the mixed solution, and the mixture is stirred at 80°C for 120 minutes and then cooled to room temperature to obtain a composite polyamic acid solution;
[0077] Step 3, vacuum degassing and film making: the composite polyamic acid solution is subjected to vacuum degassing treatment, and the degassing composite polyamic acid solution is scraped onto a high-temperature resistant boronized glass plate with a scraper, placed in an oven and heated to 80°C for 20 minutes, then heated to 130°C for 20 minutes, and finally heated to 300°C for 20 minutes to complete the high-temperature imidization treatment, the glass plate is taken out and the polyimide film is peeled off from the glass plate to obtain a polyimide film.
[0078] Example 9
[0079] The only difference from Example 2 is that in step 1, titanium sulfate is adjusted to aluminum sulfate, and the steps for preparing the polyamic acid solution are the same as in Example 1.
[0080] Preparation of polyamide membrane:
[0081] Step 1, prepare a metal ion dispersion: completely dissolve 1g of aluminum sulfate in 99g of deionized water, then add 900g of N,N-dimethylacetamide, mix and prepare a metal ion dispersion, wherein the aluminum sulfate accounts for 0.1% of the total mass of the metal ion dispersion, and set aside;
[0082] Step 2, blending, coordination and dehydration treatment: the polyamic acid solution is heated to 80°C, and the metal ion dispersion prepared in step 1 is added thereto to obtain a mixed solution, wherein the metal ion dispersion accounts for 0.01% of the mass of the mixed solution, and the mixture is stirred at 80°C for 120 minutes and then cooled to room temperature to obtain a composite polyamic acid solution;
[0083] Step 3, vacuum degassing and film making: the composite polyamic acid solution is subjected to vacuum degassing treatment, and the degassing composite polyamic acid solution is scraped onto a high-temperature resistant boronized glass plate with a scraper, placed in an oven and heated to 80°C for 20 minutes, then heated to 130°C for 20 minutes, and finally heated to 300°C for 20 minutes to complete the high-temperature imidization treatment, the glass plate is taken out and the polyimide film is peeled off from the glass plate to obtain a polyimide film.
[0084] Example 10
[0085] The only difference from Example 2 is that in step 1, titanium sulfate is adjusted to iron sulfate, and the step of preparing the polyamic acid solution is the same as that of Example 1.
[0086] Preparation of polyamide membrane:
[0087] Step 1, prepare a metal ion dispersion: completely dissolve 1g of ferric sulfate in 99g of deionized water, then add 900g of N,N-dimethylacetamide, mix and prepare a metal ion dispersion, wherein the ferric sulfate accounts for 0.1% of the total mass of the metal ion dispersion, and set aside;
[0088] Step 2, blending, coordination and dehydration treatment: the polyamic acid solution is heated to 80°C, and the metal ion dispersion prepared in step 1 is added thereto to obtain a mixed solution, wherein the metal ion dispersion accounts for 0.01% of the mass of the mixed solution, and the mixture is stirred at 80°C for 120 minutes and then cooled to room temperature to obtain a composite polyamic acid solution;
[0089] Step 3, vacuum degassing and film making: the composite polyamic acid solution is subjected to vacuum degassing treatment, and the degassing composite polyamic acid solution is scraped onto a high-temperature resistant boronized glass plate with a scraper, placed in an oven and heated to 80°C for 20 minutes, then heated to 130°C for 20 minutes, and finally heated to 300°C for 20 minutes to complete the high-temperature imidization treatment, the glass plate is taken out and the polyimide film is peeled off from the glass plate to obtain a polyimide film.
[0090] Comparative Example 1
[0091] Compared with Example 1, in this comparative example, the polyimide film is directly prepared without adding the metal ion dispersion, and the specific steps are as follows:
[0092] The steps for preparing the polyamic acid solution are the same as those in Example 1.
[0093] Vacuum degassing and film-making of polyamic acid: The polyamic acid solution is subjected to vacuum degassing treatment, and the degassing composite polyamic acid solution is scraped onto a high-temperature resistant boronized glass plate with a scraper, placed in an oven and heated to 80°C for 20 minutes, then heated to 130°C for 20 minutes, and finally heated to 300°C for 20 minutes to complete the high-temperature imidization treatment, the glass plate is taken out and the polyimide film is peeled off from the glass plate to obtain a polyimide film.
[0094] Comparative Example 2
[0095] Compared with Example 1, in this comparative example, the soluble metal salt is directly added to N,N-dimethylacetamide to prepare the polyimide film, and the specific steps are as follows:
[0096] The steps for preparing the polyamic acid solution are the same as those in Example 1.
[0097] Preparation of polyamide membrane:
[0098] Step 1, preparing a metal ion dispersion: adding 1 g of titanium sulfate to 999 g of N,N-dimethylacetamide, mixing and preparing a metal ion dispersion, wherein the titanium sulfate accounts for 0.1% of the mass of the metal ion dispersion, and the mixture is set aside;
[0099] Step 2, blending, coordination and dehydration treatment: the polyamic acid solution is heated to 80°C, and the metal ion dispersion prepared in step 1 is added thereto to obtain a mixed solution, wherein the metal ion dispersion accounts for 0.005% of the total mass of the mixed solution, and the mixture is stirred at 80°C for 120 minutes and then cooled to room temperature to obtain a composite polyamic acid solution;
[0100] Step 3, vacuum degassing and film making: the composite polyamic acid solution is subjected to vacuum degassing treatment, and the degassing composite polyamic acid solution is scraped onto a high-temperature resistant boronized glass plate with a scraper, placed in an oven and heated to 80°C for 20 minutes, then heated to 130°C for 20 minutes, and finally heated to 300°C for 20 minutes to complete the high-temperature imidization treatment, the glass plate is taken out and the polyimide film is peeled off from the glass plate to obtain a polyimide film.
[0101] Comparative Example 3
[0102] Compared with Example 1, in step 2 of this comparative example, the polyamic acid solution is directly mixed with the metal ion dispersion at room temperature, and the specific steps are as follows:
[0103] The steps for preparing the polyamic acid solution are the same as those in Example 1.
[0104] Preparation of polyamide membrane:
[0105] Step 1, prepare a metal ion dispersion: completely dissolve 1g of titanium sulfate in 99g of deionized water, then add 900g of N,N-dimethylacetamide, mix and prepare a metal ion dispersion, wherein the titanium sulfate accounts for 0.1% of the total mass of the metal ion dispersion, and set aside;
[0106] Step 2, blending, coordination and dehydration treatment: at room temperature, add the metal ion dispersion prepared in step 1 to the polyamic acid solution, stir and mix to obtain a mixed solution, wherein the metal ion dispersion accounts for 0.005% of the mass of the mixed solution, and the mixed solution is a composite polyamic acid solution;
[0107] Step 3, vacuum degassing and film making: the composite polyamic acid solution is subjected to vacuum degassing treatment, and the degassing composite polyamic acid solution is scraped onto a high-temperature resistant boronized glass plate with a scraper, placed in an oven and heated to 80°C for 20 minutes, then heated to 130°C for 20 minutes, and finally heated to 300°C for 20 minutes to complete the high-temperature imidization treatment, the glass plate is taken out and the polyimide film is peeled off from the glass plate to obtain a polyimide film.
[0108] The water content of the composite polyamic acid solutions prepared in Example 2, Example 4 to Example 7 and Comparative Example 3 was tested, and the results are shown in Table 1.
[0109] Example 80℃ constant temperature stirring time (min) Water content (%) Example 2 120 2.2 Example 4 30 8.5 Example 5 60 4.2 Example 6 90 3.1 Example 7 150 1.9 Comparative Example 3 0 13.9
[0110] The performance of the polyimide films prepared in Examples 1 to 10 and Comparative Examples 1 to 3 was tested. The results are shown in Table 2.
[0111] Table 2
[0112]
[0113] As can be seen from Table 2, the content of metal ions introduced into the polyimide in Examples 1-3 increases. Based on the coordination effect of metal ions, the interaction between the polyimide molecular chains is strengthened, and the glass transition temperature increases with the increase in content. The 5% thermal weight loss temperature of the prepared polyimide film can reach 610°C, which has excellent high temperature resistance. The mechanical properties of the polyimide film in Example 2 are the best. Example 4-7 adjusts the duration of the heating and stirring dehydration treatment on the basis of Example 2. It can be seen from the water content detection results in Table 1 that the treatment time is extended, which can reduce the moisture content in the composite polyamic acid solution. It can be seen from the results in Table 2 that the water content in the composite polyamic acid solution is reduced, and the thermal stability and mechanical properties of the polyimide film are enhanced. Example 8-10 introduces different metal ions into the polyimide. Compared with the polyimide film prepared without introducing metal ions in Comparative Example 1, the elongation at break, the breaking strength and the thermal weight loss temperature are significantly increased, and the performance is far better than that of Comparative Example 1. In Comparative Example 2, a soluble metal salt is directly added to N,N-dimethylacetamide. Since the metal salt is insoluble in DMAC, the metal salt cannot be dissociated and exists in the form of a metal salt. After being added to the polyamic acid solution, it cannot play a coordination role in the form of metal ions and exists in the solution in a granular form. During the high-temperature imidization treatment, the film surface forming the continuous phase is hindered, causing it to break and unable to form a film. During the stirring treatment at room temperature in Comparative Example 3, due to the presence of a large amount of water in the composite polyamic acid, the water absorption of the polyimide during the high-temperature imidization treatment causes gelation, and agglomeration and caking appear on the film surface.
[0114] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0115] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an ultrahigh temperature resistant polyimide film, characterized in that: The steps include: Step 1, preparing a metal ion dispersion: dissolving a soluble metal salt in water, adding a polar organic solvent, and mixing to prepare a metal ion dispersion for later use; Step 2, preparing a polyamic acid solution: polycondensing a dianhydride monomer and a diamine monomer in a polar organic solvent to form a polyamic acid solution for later use; Step 3, blending, coordination and dehydration treatment: heating the polyamic acid solution to 80-90° C., adding the metal ion dispersion prepared in step 1 thereto to obtain a mixed solution, stirring at a constant temperature and then cooling to room temperature to obtain a composite polyamic acid solution; Step 4: vacuum degassing and film making: the composite polyamic acid solution is subjected to vacuum degassing treatment, followed by film coating, and subjected to high-temperature imidization treatment to obtain a polyimide film.
2. The method for preparing an ultrahigh temperature resistant polyimide film according to claim 1, characterized in that: The soluble metal salt accounts for 0.1%-0.5% of the total mass of the metal ion dispersion.
3. The method for preparing an ultrahigh temperature resistant polyimide film according to claim 1, characterized in that: The mass ratio of water to polar organic solvent in the metal ion dispersion is 0.9-1:
9.
4. The method for preparing an ultrahigh temperature resistant polyimide film according to claim 1, characterized in that: The soluble metal salt is one of copper sulfate, aluminum sulfate, iron sulfate and titanium sulfate.
5. The method for preparing an ultrahigh temperature resistant polyimide film according to claim 1, characterized in that: In step 1 and step 2, the polar organic solvent is one of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone.
6. The method for preparing an ultrahigh temperature resistant polyimide film according to claim 1, characterized in that: In step 3, the metal ion dispersion is 0.005%-0.02% of the total mass of the mixed solution.
7. The method for preparing an ultrahigh temperature resistant polyimide film according to claim 1, characterized in that: In step 3, the constant temperature stirring time is 30-150 min.
8. The method for preparing an ultrahigh temperature resistant polyimide film according to claim 1, characterized in that: The polyamic acid solution is obtained by polycondensation reaction of 4,4'-diaminodiphenyl ether and pyromellitic acid dianhydride.
9. An ultra-high temperature resistant polyimide film, characterized in that: The method is described in any one of claims 1 to 8.
10. The ultra-high temperature resistant polyimide film according to claim 9, characterized in that: The thermal weight loss temperature of the ultra-high temperature resistant polyimide film when losing 5% of its weight is ≥570°C.
Citation Information
Cited By
High-light-transmittance polyimide resin and preparation method thereof
CN121574370A